LANGUAGE USE IN OLA ROTIMI’S 'THE GODS ARE NOT TO BLAME': A PSYCHOLOGICAL PERSPECTIVE - ANIGBOGU, Ngozi Chidinma; AHIZIH, Festus C (Socialscientia: Journal of Social Sciences and Humanities, 2020)
Language plays pivotal roles in the perception of emotions. It is a veritable tool for conveying emotions overtly and covertly. An intrinsic relation exists between language and emotions. Speakers of a language express their emotions directly through the use of language. Language is particularly relevant in representing abstract categories and shapes how individuals construe meaning of affective states. Therefore, this paper examines the use of language in conveying emotions in Ola Rotimi’s “The gods are not to Blame”. It particularly highlights the emotional language used in the drama. It is discovered that Ola Rotimi employed proverbs, incantations, metaphor, simile and apostrophe to express emotions vividly. These expressions and figurative language are overtly used to express emotions of anger, fear, distrust, suspicion, hatred, admiration and the like. It is also discovered that emotional language is rooted in culture and environment. The study draws theoretical insights from psychological constructionist theory and the Conceptual Act Theory in the discussion of emotions and language. Therefore, language involving emotions reflects specific and obvious psychological and behavioural angles of human experience and situations.